Non-ferrous metal of the Horom necropolis - Gevorgyan, Aram (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
Horom is a key archaeological site of the Bronze and Early Iron Ages in the Shirak region. Intensive archaeological excavations were carried out at this multi-layer settlement in 1990s, thanks to the collaborative efforts of the Armenian and American specialists. Valuable materials of the Bronze, Early Iron Ages and the Urartian period were discovered as a result of the project.